2013
DOI: 10.3349/ymj.2013.54.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post Biopsy Digital Rectal Compression on Improving Prostate Cancer Staging Using Magnetic Resonance Imaging in Localized Prostate Cancer

Abstract: PurposeTo evaluate the effectiveness of digital rectal-compression immediately after transrectal prostate biopsy (P-bx) for improving the accuracy of prostate cancer (PCa) staging.Materials and MethodsBetween July 2008 and June 2010, 94 consecutive patients who had a radical prostatectomy were included in our retrospective analysis. The exclusion criteria included a history of previous P-bx and surgery, a biopsy performed in another hospital, a number of biopsy cores different from 12, or a condition interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been shown that the suspicious areas on magnetic resonance imaging (MRI) scans correlate well with location of malignant lesions in post-radical prostatectomy pathological specimens 7,9. In our present study, we aim to evaluate the correlation of the tissue mapping from our robotic indentation system with suspicious areas suggestive of malignancy on MRI scans.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that the suspicious areas on magnetic resonance imaging (MRI) scans correlate well with location of malignant lesions in post-radical prostatectomy pathological specimens 7,9. In our present study, we aim to evaluate the correlation of the tissue mapping from our robotic indentation system with suspicious areas suggestive of malignancy on MRI scans.…”
Section: Introductionmentioning
confidence: 96%
“…Technological advancement had led to mechanical systems providing tactile and kinesthetic feedback to the operator 7. Ahn, et al8 reported differences in the mean elastic modulus of regions containing cancer and normal prostate tissues, using a motorized indenter in ex vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…T 2 -weighted imaging (T 2 WI), in which tumour tissue appears hypointense relative to the normal peripheral tissue, 2 has been used for morphological prostate tumour detection and localization, but the specificity of T 2 WI is low because benign prostatic hyperplasia, prostatitis, fibrosis and postbiopsy haemorrhage also cause T 2 hypointensities. [3][4][5] In addition, some prostate tumours appear normal on T 2 WI, leading to low sensitivity of this method. 6,7 Functional MR techniques (such as dynamic contrast-enhanced MRI [DCE-MRI], diffusion-weighted imaging [DWI], and magnetic resonance spectroscopy [MRS]) have been used to increase the diagnostic accuracy of MR in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%